2013
DOI: 10.1136/bmj.f4240
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthy behaviours and disability in older adults: Three-City Dijon cohort study

Abstract: Objectives To examine the individual and combined associations of unhealthy behaviours (low/intermediate physical activity, consuming fruit and vegetables less than once a day, current smoking/short term ex-smoking, never/former/heavy alcohol drinking), assessed at start of follow-up, with hazard of disability among older French adults and to assess the role of potential mediators, assessed repeatedly, of these associations.Design Population based cohort study.Setting Dijon centre of Three-City study.Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
80
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 54 publications
(48 reference statements)
10
80
3
2
Order By: Relevance
“…We did not make a distinction between necessary and unnecessary polypharmacy, using only the total amount of prescription drugs when defining this phenomenon, and this could potentially contribute to elucidation of this dilemma. The unhealthy behaviors put the patient at risk of increased morbidity, mortality, and functional decline [33,37] and can possibly lead to unnecessary use of medications to reduce such risks at the expense of far more effective nonpharmacological measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not make a distinction between necessary and unnecessary polypharmacy, using only the total amount of prescription drugs when defining this phenomenon, and this could potentially contribute to elucidation of this dilemma. The unhealthy behaviors put the patient at risk of increased morbidity, mortality, and functional decline [33,37] and can possibly lead to unnecessary use of medications to reduce such risks at the expense of far more effective nonpharmacological measures.…”
Section: Discussionmentioning
confidence: 99%
“…2. Unhealthy lifestyle habits of patients-set as a dichotomous variable; it encompassed at least two of four unhealthy behaviors such as sedentary lifestyle (i.e., physical inactivity, defined as lack of both walking at least a hour per day and exercising at least once per week or engaging in physical activity to a lesser extent than those allowed by the patient's objective health status if he/she was unable to walk, and exercise at the mentioned minimum frequency and duration due to severity of the existing diseases), improper nutrition (consuming fruits and vegetables less than once daily), active smoking or heavy alcohol consumption (intake of more than three drinks per day for men and more than two drinks daily for women); criteria for identifying bad lifestyle habits were taken from the recently published study by Artaud F et al, who found certain unhealthy behaviors to be associated with a significantly increased risk of disability in a large population-based cohort of communitydwelling older patients in France [33]. 3.…”
Section: Potential Risk Factorsmentioning
confidence: 99%
“…As for the intra-and extra-individual factors, the disablement process asserts that these factors serve as buffers, which may increase the individual's capacity or decrease environmental demands in an attempt to retard or reverse the progression of disablement. Intra-individual factors, including better social relations, a healthier lifestyle, and LTAs, play roles in increasing older adults' functional capacities and preventing physical deterioration (Artaud et al, 2013;Boyle, Buchman, Wilson, Bienias, & Bennett, 2007;James, Boyle, Buchman, & Bennett, 2011;Mendes de Leon, Gold, Glass, Kaplan, & George, 2001;Tak, Kuiper, Chorus, & Hopman-Rock, 2013). Extraindividual factors, such as using assistive devices and technology, are seen as external supports that help older adults achieve better functioning.…”
Section: Studies Have Shown That Older Adults With Disabilities In Admentioning
confidence: 96%
“…Despite the extensive evidence showing that FV consumption improves the health of young adults, the extent to which these benefits apply to older adults has received relatively little attention. The few existing prospective data suggest that consuming FVs during old age may help prevent the onset of depression (13), cognitive decline (14), mobility limitations, and disability (15)(16)(17)(18) while positively influencing muscle strength (19,20) and bone mineral status (21,22). In addition, the consumption of FVs in older adults has shown to decrease the risk of disease-specific and allcause mortality (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%